2016
DOI: 10.3390/atmos7020022
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends and Abrupt Features of Extreme Temperature in Mainland China from 1960 to 2010

Abstract: Studies based on the 10th (90th) percentiles as thresholds have been presented to assess moderate extremes in China and globally. However, there has been notably little research on the occurrences of high extremes of warm days and hot days (TX95p and TX99p) and cold nights and very cold nights (TN05p and TN01p), based on the 95th and 99th (5th and 1st) percentiles of the daily maximum (minimum) temperature data at a certain station in the period 1971-2000, which have more direct impacts on society and the ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Moreover, the average phases of all of the climate factors except for annual precipitation abruptly changed, consequently affecting the apple quality of all of the apple-producing regions. Previous studies on the effect of climate change on apple production have primarily focused on the aspects of climate resources, phenological periods, production, and hazard risks [35][36][37][38]. Based on the production scale and market percentage of China, the major developing tendency is to control the scale with stable yields while improving quality in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the average phases of all of the climate factors except for annual precipitation abruptly changed, consequently affecting the apple quality of all of the apple-producing regions. Previous studies on the effect of climate change on apple production have primarily focused on the aspects of climate resources, phenological periods, production, and hazard risks [35][36][37][38]. Based on the production scale and market percentage of China, the major developing tendency is to control the scale with stable yields while improving quality in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that over the last several decades, the plant growth seasons in the northern hemisphere have gradually extended, which leads to an increase in carbon sequestration in highlatitude areas. 15 In China, many studies show similar trends in most regions using ground observation and satellite monitoring, Fang et al 16 and Zheng et al 17 discussed the effect of global warming on plant phenological changes, and the results show that the response of ahead (or delay) of phenophase to increasing (or decreasing) of temperature was nonlinear. Zhang, 18 Lu et al, 19 Li et al, 20 He et al, 21 Fang et al, 22 Zhong et al, 23 Wang et al, 24 and Xie et al 25 studied the trend of plant phenology and its responses to climatic change over different areas in China.…”
Section: Introductionmentioning
confidence: 94%
“…The annual average temperature is 10−13 • C in Southern Xinjiang and less than 10 • C in Northern Xinjiang. The extreme maximum temperature has reached 48.9 • C in Eastern Xinjiang's Turpan Basin while an extreme minimum temperature of −51.5 • C occurs in Northern Xinjiang's Keketuohai (Fang et al, 2016). The precipitation in Xinjiang is low overall, with an average annual precipitation of approximately 150 mm and a distinct regional difference.…”
Section: Study Areamentioning
confidence: 99%